1978
DOI: 10.1180/minmag.1978.042.321.01
|View full text |Cite
|
Sign up to set email alerts
|

Feldspars and fluids in cooling plutons

Abstract: SUMMARY. Alkali feldspars in plutonic igneous rocks vary both in their exsolution textures and in the structural state of their components. The primary factor leading to this diversity is the availability of hydrothermal fluids during their cooling history. In many plutons feldspar variation is related to degree of fractionation as indicated by rock chemistry. The variation reflects build-up of water with magmatic evolution and implies that fluids did not circulate freely in the intrusives in the temperature r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
4

Year Published

1982
1982
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(71 citation statements)
references
References 26 publications
2
65
0
4
Order By: Relevance
“…This is perhaps most evident in sample 38-1 which may contain a significant amount of intergrown triclinic K-feldspar. How ever, probably the most notable feature is the overall predomi nance of the monoclinic structural state for pegmatitic K-feldspars (e.g., note the sharp (131)K reflection for sample 22C) considering their formation in a fluid-rich environment (Parsons and Boyd, 1971;Parsons, 1977). In contrast to the aforemen tioned samples, development of triclinic phases occurs in samples 29B, 32 and 49, with the latter samples clearly reflecting the presence of both monoclinic and triclinic phases.…”
Section: Mineral Chemistrymentioning
confidence: 74%
See 1 more Smart Citation
“…This is perhaps most evident in sample 38-1 which may contain a significant amount of intergrown triclinic K-feldspar. How ever, probably the most notable feature is the overall predomi nance of the monoclinic structural state for pegmatitic K-feldspars (e.g., note the sharp (131)K reflection for sample 22C) considering their formation in a fluid-rich environment (Parsons and Boyd, 1971;Parsons, 1977). In contrast to the aforemen tioned samples, development of triclinic phases occurs in samples 29B, 32 and 49, with the latter samples clearly reflecting the presence of both monoclinic and triclinic phases.…”
Section: Mineral Chemistrymentioning
confidence: 74%
“…This is found regardless of rock type (i.e., mon zogranite versus pegmatite) and, therefore, the simple but gener alized relationship of increasing ordering with increasing fluid pressure (e.g., Parsons and Boyd, 1971;Parsons, 1977;Parsons and Brown, 1984) does not apppear to strictly apply here. A similar situation exists in other large granitoid batholiths, such as parts of the nearby SL George Batholith of southern New Brun swick (Cherry and Trembath, 1978) or the Wiborg rapakivi massif of southern Finland (Vorma, 1971).…”
Section: Implications Of Structural States Of Alkali Feldsparsmentioning
confidence: 99%
“…Several studies showed that abundance of exsolution textures in alkali feldspar indicates extensive structural rearrangement of magmatic alkali feldspar at low (=400 °C) temperature (e.g. Parsons 1978;Brown and Parsons 1989;Worden et al 1990;Lee et al 1995;Walker et al 1995). The turbidity in alkali feldspars points to recrystallization driven by infiltration of aqueous fluid.…”
Section: T M Qadhimentioning
confidence: 99%
“…The turbidity in alkali feldspars points to recrystallization driven by infiltration of aqueous fluid. According to Parsons (1978), coarse patch perthite in subsolvus feldspars developed isochemically by water-impelled dissolution and reprecipitation. This suggests that in the course of recrystallization the system remained closed.…”
Section: T M Qadhimentioning
confidence: 99%
“…This means that the Scourian mesoperthites probably crystallized within 50~ of the critical temperature of the ternary feldspar solvus at An12. Parsons (1978) estimated that for the constant ratio Ab63Or37 the ternary feldspar solvus increases by 32 ~ % anorthite. This suggests a ternary solvus temperature of 1040~ for the composition (Abo.taOro.37)ssAn12.…”
Section: Copyright the Mineralogical Societymentioning
confidence: 99%